Multiple coil closure of isolated aortopulmonary collateral - Padhi Sumanta; Bakshi Kinjal; Shastri Ram (Wolters Kluwer Medknow Publications, 2010)
A 7-month-old girl was diagnosed to have large aortopulmonary collateral during evaluation for congestive heart failure. There was no other evidence of cardiopulmonary disease. The collateral was successfully closed with multiple coils delivered sequentially. We describe the issues associated during closure of the aortopulmonary collateral in this case. To the best of our knowledge, this is the first reported case of large aortopulmonary collateral presenting with heart failure in an otherwise structurally normal heart that was closed successfully with multiple coils delivered sequentially.